2018
DOI: 10.1080/02652048.2018.1526341
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polymer molecular weight and cell seeding density on viability of cells entrapped within PEGDA hydrogel microspheres

Abstract: Cell microencapsulation can be used in tissue engineering as a scaffold or physical barrier that provides immunoisolation for donor cells. When used as a barrier, microencapsulation shields donor cells from the host immune system when implanted for cell therapies. Maximizing therapeutic product delivery per volume of microencapsulated cells necessitates first optimising the viability of entrapped cells. Although cell microencapsulation within alginate is well described, best practices for cell microencapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…Further, by observation at higher weight percent gels, colonies began to have a more elongated rather than spherical morphology (Figure b), implying matrix forces may be acting to create this deformation. It is possible that at these higher weight percent formulations, an increase in hydrogel swelling (upon equilibration) applies a swelling force to the encapsulated colonies, decreasing their survival . In this case, decreased survival could also be attributed to osmotic effects .…”
Section: Colony Survival Exhibits Moduli Dependencementioning
confidence: 99%
“…Further, by observation at higher weight percent gels, colonies began to have a more elongated rather than spherical morphology (Figure b), implying matrix forces may be acting to create this deformation. It is possible that at these higher weight percent formulations, an increase in hydrogel swelling (upon equilibration) applies a swelling force to the encapsulated colonies, decreasing their survival . In this case, decreased survival could also be attributed to osmotic effects .…”
Section: Colony Survival Exhibits Moduli Dependencementioning
confidence: 99%
“…Although cells were encapsulated using 10 kDa PEGDA, the stain is broadly applicable to other materials used for cell microencapsulation. We previously established the mesh size of our 10 % 10 kDa PEGDA hydrogels to be 280 Å and that dextran molecules up to 20 kDa were readily released from these hydrogels [ 15 ]; the molecular weight of calcein is 622.55 g/mol. Considering that the mesh size of encapsulated cells must be large enough to permit nutrient and waste exchange as well as entry of serum proteins, it is likely that calcein could be used to assess mineralization in many cell microencapsulation systems.…”
Section: Discussionmentioning
confidence: 99%
“…34 Protein release rate following physical encapsulation in a hydrogel is inversely proportional to the size of the payload and directly proportional to the pore or mesh size of the biomaterial. 35,36 The Kloxin group demonstrated that mesh size of a hydrogel could be used to predict release and retention of proteins of different sizes. 36 Using a PEG-based library of materials, they systematically demonstrated that the elasticity and swelling of the material directly correlated to mesh size, and that mesh size, in turn, impacted the release of a range of proteins, including aprotinin (7 kDa), myoglobin (17 kDa), BSA (66 kDa), lactoferrin (77 kDa), and thyroglobulin (663 kDa).…”
Section: Physical Encapsulationmentioning
confidence: 99%